2022
DOI: 10.1136/neurintsurg-2022-018895
|View full text |Cite
|
Sign up to set email alerts
|

Direct to angiosuite strategy versus standard workflow triage for endovascular therapy: systematic review and meta-analysis

Abstract: BackgroundReducing stroke workflow times when performing endovascular thrombectomy is associated with improvement in clinical outcomes. We compared outcomes among large vessel occlusion (LVO) stroke patients following the direct to angiosuite (DTAS) strategy versus standard workflow (SW) when undergoing endovascular therapy.MethodsWe conducted a systematic review and meta-analysis to compare rates of functional outcomes, reperfusion, symptomatic intracranial hemorrhage (sICH) and stroke workflow metrics. We in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…Time from admission to reperfusion has been repeatedly associated with functional outcome and the effect of DTAS reducing this is beyond doubt the reason after the consistent evidence published in the last few years. In the ANGIOCAT trial, although the DTCT group presented a remarkably low median door to puncture time of 42 min, the same interval was only 18 min when the DTAS was followed, similar than previously published in pilot and collaborative studies 7 9 10 17–19. On the other hand, the ANGIOCAT trial is the first study which compared protocols in patients with a confirmed LVO whether or not they received mechanical thrombectomy, and showed that DTAS was associated with an increased rate of EVT (100% of DTAS vs 89% of DTCT patients).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Time from admission to reperfusion has been repeatedly associated with functional outcome and the effect of DTAS reducing this is beyond doubt the reason after the consistent evidence published in the last few years. In the ANGIOCAT trial, although the DTCT group presented a remarkably low median door to puncture time of 42 min, the same interval was only 18 min when the DTAS was followed, similar than previously published in pilot and collaborative studies 7 9 10 17–19. On the other hand, the ANGIOCAT trial is the first study which compared protocols in patients with a confirmed LVO whether or not they received mechanical thrombectomy, and showed that DTAS was associated with an increased rate of EVT (100% of DTAS vs 89% of DTCT patients).…”
Section: Discussionsupporting
confidence: 69%
“…Similarly, to the percutaneous coronary intervention protocols in acute myocardial infarction, several case–control studies have shown that transporting stroke patients directly to the angiosuite is safe, feasible and results in a significant reduction in median door to treatment times down to 16 min and potentially higher chances of good outcomes 4 6–9. Several meta-analyses10 11 and one randomized clinical trial (ANGIOCAT trial) have recently confirmed these data 12…”
Section: Introductionmentioning
confidence: 94%
“…The data demonstrate a significant decrease in door-to-groin puncture times via the DTA approach (ranging from 29 to 35 minutes). Mohammaden et al and Galecio-Castillo et al 43 also demonstrate functional benefit at 90 days via the DTA approach.…”
Section: Meta-analysesmentioning
confidence: 92%
“…We identified 10 retrospective studies with at least 25 patients (per study) triaged using the DTA approach (Jadhav et al, 30 Ribo et al, 31 Psychogios et al, 5 Mendez et al, 32 Psychogios et al, 33 Bouslama et al, 34 Requena et al, 35 Mendez et al, 36 Sarraj et al, 37 and Regenhardt et al 38 ) and 2 completed randomized controlled trials (Pfaff et al 39 and Requena et al 40 ; Table 1). Further, we also identified 3 meta-analyses (Brehm et al, 41 Mohammaden et al, 42 and Galecio-Castillo et al 43 ) and 3 ongoing randomized controlled trials (Table 2). 5,[30][31][32][33][34][35][36][37][38] Retrospective Data Table 1 summarizes these studies, characteristics, and results.…”
Section: What Is the Evidence For Dta?mentioning
confidence: 99%
“…Several meta-analyses have reviewed the results of the DTAS strategy on potential EVT patients compared to classical (DTCT, direct-to-emergency department) pathways [46] , [47] , [48] . All included mixed population groups of transferred and directly mothership patients.…”
Section: Dtasmentioning
confidence: 99%